PENGARUH PEMBERIAN JAGUNG (Zea mays) TERHADAP PERTUMBUHAN IKAN MAS (Cyprinus carpio) DI DESA TANJUNG MULIA KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Muhammad Khairul Saleh; Eri Yusni; Syammaun Usman (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Common carp (Cypirinus carpio) is fish consumption. It is a higheconomic value and suitable for cultivationed. This is very popular in Indonesiapeople. The Experimental wer give commercial feed and combinasion with thecorn (Zea mays). Feed this were give 3 times a day, and the corn (Zea mays)weregive for the treatment 1(1%), treatment 2(2%), and treatment 3 (3%, but to thecommercial feed were give 3% for the all treatment. During 3 mounth of thisstudys were used 9 cages,eat 1 cages were put of 50 fish and the results werefound of treatment 3(3%) were to be better than treatment 1 and treatment 2.Body weight of treatment 3 were found of 170 gram, followed treatment 2 of 120gram and treatment 1 of 87 gram. The body length treatment 3 were found of 16 –18 cm, followed treatment 2 of 15 – 17 cm and treatment 1 of 13 – 15 cm.Keyword: Cypirinus carpio,Common carp, Feeding, Zea mays.